2002
DOI: 10.2337/diabetes.51.2.462
|View full text |Cite
|
Sign up to set email alerts
|

Normalization of Plasma Glucose Concentration by Insulin Therapy Improves Insulin-Stimulated Glycogen Synthesis in Type 2 Diabetes

Abstract: Considerable evidence suggests that skeletal muscle insulin resistance is an inherent feature of type 2 diabetes and contributes to the pathogenesis of the disease. In patients with poorly controlled diabetes, hyperglycemia is thought to produce additional insulin resistance in muscle. The magnitude and nature of hyperglycemia-induced insulin resistance is not known. The purpose of the present study was to determine the biochemical mechanisms responsible for increased insulin-stimulated glucose disposal after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 83 publications
4
19
0
Order By: Relevance
“…In our diabetic population there was no activation of GS by insulin infusion in physiological concentrations (40 mU ⅐ m Ϫ2 ⅐ min Ϫ1 ), which is consistent with observations in a recent study of poorly controlled obese diabetic subjects (48). Because this defect was not caused by defects in the signaling steps generally believed to be involved in insulin activation of GS, what mechanisms are involved?…”
Section: Discussionsupporting
confidence: 91%
“…In our diabetic population there was no activation of GS by insulin infusion in physiological concentrations (40 mU ⅐ m Ϫ2 ⅐ min Ϫ1 ), which is consistent with observations in a recent study of poorly controlled obese diabetic subjects (48). Because this defect was not caused by defects in the signaling steps generally believed to be involved in insulin activation of GS, what mechanisms are involved?…”
Section: Discussionsupporting
confidence: 91%
“…Despite a reduced activity in muscle of type 2 diabetes, glycogen synthase expression is normal, suggesting altered regulation. Normalization of plasma glucose concentration in type 2 diabetic patients by diet or insulin therapy improves insulinstimulated glycogen synthesis, suggesting that these abnormalities may be secondary to hyperglycemia per se (253,254). In an interesting study of monozygotic twin pairs discordant for type 2 diabetes, insulin stimulation of glycogen synthase expression was only impaired in muscle of the affected twin (255).…”
Section: Role Of Impaired Glycogen Synthesis and Breakdown In Human Tmentioning
confidence: 99%
“…We and others have demonstrated that short-term insulin intensive therapy (IT) is effective to reduce hyperglycemic-induced insulin resistance (17,18). As insulin resistance would be reduced whereas circulating insulin level is not decreased or even increased during IT, we hypothesized that IT would be an optimal regimen to determine whether it is the reduction of insulin resistance or circulating insulin per se that is responsible for serum SHBG elevation.…”
Section: Introductionmentioning
confidence: 99%